2017
DOI: 10.1136/emermed-2015-204924
|View full text |Cite
|
Sign up to set email alerts
|

Can a partnership between general practitioners and ambulance services reduce conveyance to emergency care?

Abstract: BackgroundEmergency services are facing increasing workload pressures, and new models of care are needed. We evaluate the impact of a service development involving a partnership between emergency ambulance crews and general practitioners (GPs) on reducing conveyance rates to the Hospital Emergency Department(ED) .MethodsThe service model was implemented in the West Midlands of England. Call handlers identified patients with needs that could be addressed by a GP using locally agreed criteria. GPs supported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Furthermore, the ED is an attractive source of medical care because of perceived convenience and access to specialised care and ancillary investigations (pathology and radiology) . Strategies to reduce demand may include primary and secondary prevention, pre‐hospital diversion and telephone advice . Reducing ED presentations may reduce hospital costs …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ED is an attractive source of medical care because of perceived convenience and access to specialised care and ancillary investigations (pathology and radiology) . Strategies to reduce demand may include primary and secondary prevention, pre‐hospital diversion and telephone advice . Reducing ED presentations may reduce hospital costs …”
Section: Introductionmentioning
confidence: 99%
“…The search for primary studies identified 4653 references. Of those, 47 were potentially relevant (Figure ), and we examined the full text . However, none fulfilled our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, R⊘rtveit found that the EMCC has problems with over and under triage, and having a GP on the scene was suggested as a solution to this challenge [ 16 ]. A recent study from England also found that involving GPs improved prehospital treatment by providing better treatment and reducing the number of patients who were admitted to hospital [ 17 ]. Despite reporting having a large role in local emergency medicine, the GPs in our survey reported that they only took part in a select number of ambulance call outs.…”
Section: Discussionmentioning
confidence: 99%